They never knew : the victims of nuclear testing - Cheney, Glenn Alan. frey50 (New York : F. Watts, 1996)
Examines the American government's role in developing nuclear weapons and conducting atomic testing, focusing on the effects of radiation on humans and the victims' attempts to sue the government for compensation.
Keywords: Nuclear warfare -- Health aspects; Nuclear weapons -- Testing -- Health aspects; Nuclear warfare -- Health aspects; Nuclear weapons -- Testing -- Health aspects; Radiation victims